ADLERIAN STRATEGIES IN WILLY WONKA’S CHARACTER IN TIM BURTON’S FILM CHARLIE AND THE CHOCOLATE FACTORY - Amanda Putri Wira Dharma; Mardliya Pratiwi Zamruddin; Famala Eka Sanhadi Rahayu (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
This study aims to find out how Willy Wonka's character in the Charlie and the Chocolate Factory film strived to overcome his inferiority state to achieve superiority in his life using the Adlerian strategy stages of Alfred Adler's individual psychology theory. This study was qualitative research with a psychoanalysis approach. The data from this study were the actions, dialogues, and other character’s narrations that are depicted in clip scenes from the film. In analyzing the data, the researcher identified each scene that depicted the factors that influenced the feelings of inferiority that appeared in Willy Wonka's character and analyzed how Willy Wonka strived for superiority. The results of this study indicated that there is a representation of Willy Wonka's inferior feelings because of his unpleasant childhood compared to his friends who had a pleasant childhood. This feeling of Willy's inferiority is triggered by several factors namely lifestyle, parenting patterns, and birth orders. After going through a period of inferiority, Willy finally achieved success in his life goals of becoming a famous chocolate maker and making his own chocolate factory. Willy's way to overcome these inferior feelings is applying superiority complex proposed by Alfred Adler which consists of creative-self, social interest, confidence, ambition, and striving for superiority.